The Ankyrin Repeat Domain Controls Presynaptic Localization of Drosophila Ankyrin2 and Is Essential for Synaptic Stability - Weber, Tobias; Stephan, Raiko; Moreno, Eliza; Pielage, Jan (Frontiers in Cell and Developmental Biology, 2019)
The structural integrity of synaptic connections critically depends on the interaction between synaptic cell adhesion molecules (CAMs) and the underlying actin and microtubule cytoskeleton. This interaction is mediated by giant Ankyrins, that act as specialized adaptors to establish and maintain axonal and synaptic compartments. In Drosophila, two giant isoforms of Ankyrin2 (Ank2) control synapse stability and organization at the larval neuromuscular junction (NMJ). Both Ank2-L and Ank2-XL are highly abundant in motoneuron axons and within the presynaptic terminal, where they control synaptic CAMs distribution and organization of microtubules. Here, we address the role of the conserved N-terminal ankyrin repeat domain (ARD) for subcellular localization and function of these giant Ankyrins in vivo. We used a P[acman] based rescue approach to generate deletions of ARD subdomains, that contain putative binding sites of interacting transmembrane proteins. We show that specific subdomains control synaptic but not axonal localization of Ank2-L. These domains contain binding sites to L1-family member CAMs, and we demonstrate that these regions are necessary for the organization of synaptic CAMs and for the control of synaptic stability. In contrast, presynaptic Ank2-XL localization only partially depends on the ARD but strictly requires the presynaptic presence of Ank2-L demonstrating a critical co-dependence of the two isoforms at the NMJ. Ank2-XL dependent control of microtubule organization correlates with presynaptic abundance of the protein and is thus only partially affected by ARD deletions. Together, our data provides novel insights into the synaptic targeting of giant Ankyrins with relevance for the control of synaptic plasticity and maintenance.